Pelatihan English For Tourist Guide Untuk Himpunan Pramuwisata Indonesia (HPI) Kota Pekanbaru - Syaifullah; Refika Andriani (Universitas Lancang Kuning, 2021)
According to the Indonesian Tourism Association statutes 2011, tour guideshave several duties, one of them is improving consecutively their professionalism. The indicator which can be indicated from their professionalism is their capability in doing well communication with their colleague or tourist particularly communication in English. Related to the daily activity, wheneverI invite them to make an English tour none of them ready to execute it. It one of the symptoms shows that they have limit capability in English communication. To solve this problem, I and team have trained them in English for tourist guide in several meetings. As a result, this English tourist guide training can develop their capability in making English communicationas long as they want to practice their English with their colleague or by them selves